The relationship between sex steroids (E2, progesterone, and AMH) levels and severity and fatality of COVID-19: A systematic review. Issue 3 (March 2023) - Qaderi, Kowsar; Hosseinirad, Hossein; Kalhor, Mehri; Zangeneh, Sanaz; Pournaghi, Marjaneh; Khodavirdilou, Rasa; Keshavarz, Maryam; Eghdampour, Farideh; Mirmolaei, Seyedeh Tahereh; Jesmani, Younes; Barjasteh, Samira; Mallah, Manthar Ali; et al.
Abstract: Sex steroids are powerful modulators of the immune system and they may affect the immune response and inflammatory consequences of COVID-19. This systematic review aims to explore the impact of sex steroids on COVID-19 mortality and complications. We looked up the keywords of the study in Scopus, PubMed, and Web of Science. All related original articles published in English, as of October 16, 2021, were reviewed to be included in our research. Concerns regarding the effect of sex hormones on COVID-19, eight full texts have been identified for the conclusion. In these studies, the relationship between estradiol and COVID-19 mortality has been mentioned. The most significant findings were the higher COVID-19 mortality rate in men, compared to women; also, in menopausal women compared to younger women and who received estradiol. In two studies, oral contraceptive pills had a protective effect on the morbidity of SARS-CoV-2 infection. In a randomized controlled trial, subcutaneous injection of progesterone in hospitalized men significantly reduced their symptoms and need for oxygen therapy. Hormone replacement therapy was positively associated with reducing COVID-19 symptoms. Although the results were insufficient for a conclusion, this study represents estrogen as an appropriate pharmacological method for preventing and diminishing the inflammation related to COVID-19 disease. However, future prospective studies and clinical trials are needed to clarify and approve this protective effect.